Mapping of MSME Financial Studies: Bibliometric Analysis - Maruf, Fatmah; Darman, Darman (Eastasouth Institute, 2025)
This study aims to map the intellectual structure, evolutionary trends, and thematic clusters in the literature on Micro, Small, and Medium Enterprises (MSMEs) Finance through Bibliometric Analysis. Data were collected from the Scopus database with a total of 64 articles rigorously selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol. The results of the performance analysis indicate a significant acceleration of publications in the last two years (2024–2025), which collectively represent 42.1% of the entire corpus. Geographically, research is highly concentrated in developing countries, with India (34 documents) and Indonesia (14 documents) being the main contributors and India acting as a hub for global collaboration. Keyword co-occurrence analysis identified three main conceptual clusters: (1) Core Entity Cluster (Msme); (2) Funding Issues Cluster (Finance, Financial inclusion, Access to finance); and (3) Outcome/Impact Cluster (Firm performance). Furthermore, Technology Adaptation emerged as a key thematic trend, indicating a shift in research focus toward digital solutions (FinTech). These findings provide a clear roadmap for researchers and critical insights for policymakers in designing interventions that target financial constraints and harness the potential of digital innovation for MSME sustainability.